CONULARIID-LIKE FOSSIL FROM THE VENDIAN OF RUSSIA: A METAZOAN CLADE ACROSS THE PROTEROZOIC/PALAEOZOIC BOUNDARY - Ivantsov A.Yu.; Fedonkin M.A. (My University, 2002)
A conulariid–like fossil is described for the first time from Upper Vendian (late Neoproterozoic) deposits. Vendoconularia triradiata gen. et sp. nov. is found with other fossils in poorly cemented, siliciclastic deposits of the lower part of the Ust’–Pinega Formation, exposed in the middle reaches of the Onega River, north of the Russian Platform. This fossil assemblage, stratigraphically lowermost in the region, includes Swartpuntia Narbonne, endemic Ventogyrus Ivantsov and Grazhdankin, Calyptrina–like tubular forms, and other new, as yet undescribed, species. Vendoconularia is described here using morphological terms developed for conulariids owing to their striking similarity. However, the six faces of the conical test and three–fold symmetry may reflect some phylogenetic connection with the larger clade of Trilobozoa, a cnidarian class that radiated during the Late Vendian–Early Cambrian and then became extinct.
Keywords: Vendian; conulariid; Russia; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский